High-dose Erythropoietin Has No Long-term Protective Effects in Sheep with Reperfused Myocardial Infarction - Olea, Fernanda Daniela (2006)
High-dose erythropoietin has been claimed to be cardioprotective in experimental acute myocardial infarction. In large mammals, however, results are controversial and long-term follow-up data are lacking. We thus assessed the long-term effects of high-dose erythropoietin on left ventricular infarct size and function in an ovine model of reperfused myocardial infarction. After 90 minutes of coronary occlusion followed by reperfusion, sheep received recombinant human erythropoietin (rhEPO) 3000 units/kg on 3 consecutive days (rhEPO group, n=7) or vehicle (placebo group, n=6). Ten weeks later, ventricular function was assessed by echocardiography and catheterization. Infarct size, evaluated as percent fibrotic myocardium (morphometry) and by hydroxyproline quantification, was similar in both groups (morphometry: rhEPO: 22.1 +/- 5.5%, placebo: 18.1 +/- 3.3%, P not significant; hydroxyproline: rhEPO: 6.6 +/- 1.3 microg/mg wet weight, placebo: 7.1 +/- 0.9 microg/mg, P not significant). Ventricular function was diminished in the rhEPO group, as indicated by lower septal wall thickening at the infarct border zone (rhEPO: -1.9 +/- 16.4%, placebo: 20.5 +/- 17%, P<0.04), higher end systolic volume (rhEPO: 47 +/- 14.3 mL, placebo: 32.6 +/- 7.3 mL, P<0.05), and higher end diastolic pressure (rhEPO: 17 +/- 6.5 mm Hg, placebo: 10.1 +/- 2.8 mm Hg, P<0.03). In the rhEPO group, left ventricular endocardial area was larger, suggesting dilatation. High-dose erythropoietin has no cardioprotective effects in sheep with reperfused myocardial infarction.